2015
DOI: 10.1039/c5nr00040h
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity flexible Lamb-wave humidity sensors with a graphene oxide sensing layer

Abstract: This paper reports high performance flexible Lamb wave humidity sensors with a graphene oxide sensing layer. The devices were fabricated on piezoelectric ZnO thin films deposited on flexible polyimide substrates. Two resonant peaks, namely the zero order antisymmetric (A0) and symmetric (S0) mode Lamb waves, were observed and fitted well with the theoretical analysis and modelling. With graphene oxide microflakes as the sensing layer, the sensing performance of both wave modes was investigated. The humidity se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 36 publications
1
60
0
Order By: Relevance
“…In recent years, humidity measurement and monitor have been paid more and more attention for its importance and necessity in many areas such as weather prediction, historic preservation, medical/healthcare product development, industrial manufacturing, agriculture and wearable or mobile electronics [1]. For the requirements of precision, electric hygrometer gains broader concern than the traditional hair hygrometer or psychrometer, due to its sensitivity of electrical signal along with the changing of moisture content in materials.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, humidity measurement and monitor have been paid more and more attention for its importance and necessity in many areas such as weather prediction, historic preservation, medical/healthcare product development, industrial manufacturing, agriculture and wearable or mobile electronics [1]. For the requirements of precision, electric hygrometer gains broader concern than the traditional hair hygrometer or psychrometer, due to its sensitivity of electrical signal along with the changing of moisture content in materials.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the proposed QCM humidity sensor's sensitivity is much better compared with the reported QCM humidity sensors, and this is attributed to the large specific surface area and hydrophilic nature of the graphene oxide layers. The sensitivity is also related closely to the thickness of graphene oxide layers, and can be significantly enhanced with the increase of graphene oxide layer thickness [9]. As can be seen in Fig.3, the sensitivity of the QCM sensor with GO is high at medium RH values, but low at low RH values, and the linearity of f ∆ and S are also poor, which limited the use of the sensor.…”
Section: Sensitivity and Linearitymentioning
confidence: 95%
“…Although carbon nanotubes and graphene flakes are good sensitive layers owing to their large surface areas, the certain degree of hydrophobicity nature of these carbon nanomaterials have suppressed their positive effects on sensitivity. On the other hand, graphene oxide (GO) flakes are a hydrophilic material beside the common nature of nanomaterials [8], and graphene oxide as a sensitive layer is expected to enhance the sensitivity of QCM humidity sensors significantly as demonstrated by flexible and transparent surface acoustic wave based humidity sensors [9]. Yao et al firstly studied the humidity sensing characteristics of GO on QCM and obtained the relationship between frequency shift and RH [10].…”
Section: Introductionmentioning
confidence: 99%
“…For this research, only the SAW devices with wavelength of λ = 16 μm were used. Our previous work (Xuan et al 2014(Xuan et al , 2015 has demonstrated the fabricated SAW devices with a wavelength of λ = 16 μm have the Rayleigh wave mode, performed well with resonant frequencies round ~171.7 MHz and have a high sensitivity to humidity. Figure 2b and c are the photo images of the SAW device used for sensing experiments.…”
Section: Saw Sensor and Measurement Setupmentioning
confidence: 97%